Potentiometric Study on the Ternary Complexes of Chromium(III) Metal Ion at Different Ionic Strength - Kolhe, Vishnu; Saxena, Shikha; Dhingra, Vinod (Asian Journal of Chemistry, 2010)
The stepwise equilibria of 1 : 1 : 1 Cr(III)-A-L mixed ligands systems where A = salicylic acid (SA)/monosodium salt of 5-sulfosalicylic acid (SSA) and 3,5-dinitrosalicylic acid (DNSA) and L = 2-hydroxyacetophenone (HAP), 2,5-dihydroxy acetophenone (DHAP) and 5-chloro-2-hydroxyacetophenone (CHAP) have been investigated potentiometricaily at 0.05 M, 0.10 M and 0.15 M (NaNO3) ionic strengths in ethanolic-aqueous (20% v/v) medium at 25ºC.